Multiple-model control architecture for a quadrotor with constant unknown mass and inertia. (February 2021) - Outeiro, Pedro; Cardeira, Carlos; Oliveira, Paulo
Abstract: This paper presents a methodology for height and yaw angle control of a quadrotor that transports an unknown constant load added before the flight. Based on measurements from the onboard sensors, estimates of inertial parameters – mass and z-axis inertia – and state variables – vertical position, velocity, yaw angle and rate – are provided resorting to Multiple-Model Adaptive Estimators. The number and worst case performance of Kalman filters is selected based on the Baram Proximity Measure. The proposed control methods are a steady state Linear Quadratic Regulator (LQR) with integrative action for the height, and an LQR controller for the yaw angle. The overall system obtained is validated with load variations of up to 10% of the vehicle mass, both in simulation and experimentally, resorting to an off-the-shelf commercially available quadrotor.